Population Structure of Polymesoda expansa Shellfish in Mangrove Forest in Banglas Village, Meranti Islands - Anggraini, Hafidah Novi; Nasution, Syafruddin; Tanjung, Afrizal (Fakultas Perikanan dan Kelautan Universitas Riau, 2025)
Lokan (Polymesoda expansa) is a bivalve in mangrove forest areas with important ecological and economic values. The lokan population plays a role in maintaining water quality and is a source of livelihood for coastal communities. This study aims to analyze the abundance, distribution patterns, and frequency distribution of individual sizes of P. expansa in the mangrove forest of Banglas Village, Meranti Islands Regency. The research was conducted in December 2024 using a survey method to determine station locations by purposive sampling. Sampling was conducted at three stations, each consisting of three transects with plots measuring 1 × 1 m². The results showed that the highest abundance was found at Station III (±16.33 ± 5,508 ind/m²) and the lowest at Station II (8.33 ± 2,082 ind/m²). The distribution pattern of lokan at all stations is clustered (Morisita index value> 1). The frequency distribution of individual sizes showed the dominance of sizes 3.40-3.89 cm with 21 individuals. Abundance and distribution patterns of lokan are influenced by habitat conditions, human activities, and food availability. ANOVA test results showed no significant differences in abundance between stations, but there were significant differences between subzones. Knowledge of the population structure of P. expansa is vital for sustainable resource management in mangrove ecosystems